Multiproduct Firms, Import Competition and Productivity - Emmanuel Dhyne; Amil Petrin; Valerie Smeets; Frederic Warzynski (CESifo GmbH, 2024)
We study how increased import competition affects the evolution of productivity in a small open economy. We use a production survey of Belgian firms where we observe quarterly firm-product data at the 8-digit level on value and quantities sold together with firm-level labor, capital, and intermediate inputs from 1997 to 2007, a period marked by a stark decline in tariffs applied to Chinese goods. We extend the methodology developed in Dhyne et al. (2022) to estimate firm-product measures of productivity. We find that a 1% increase in the import share leads to a 1.05% gain in productivity. This elasticity translates into gains from competition over the sample period exceeding 1.2 billion euros, which is over 2.5% of the average annual value of manufacturing output in Belgium. We show firms appear to be less productive the further away from their ”core” competency product. We also find that firms respond to competition by focusing more on their core products. Instrumenting import share with changes in Chinese tariffs magnifies the effect of competition as the coefficient increases tenfold moving from OLS to IV.
Keywords: F10; 330